FINANCIAL, NON-FINANCIAL, AND MACRO-ECONOMIC FACTORS THAT AFFECT THE FIRST DAY PROFIT RATE WHEN CONDUCTING INITIAL PUBLIC OFFERING - Ruth Pranadipta; Natsir, Khairina (International Journal of Application on Economics and Business, 2023)
The intention of this research is to specify and analyze the influence of profitability, financial leverage, company age, underwriters, and inflation on the first day profit rate for firms that conduct initial public offerings on the Indonesia Stock Exchange (IDX). There were 212 firms that went public and were listed on the Indonesia Stock Exchange (IDX) for the 2016-2020 period. This study resulted in 172 companies as research samples. Purposive sampling method is a sampling technique utilized in this research. Data analysis utilized cross-sectional data with multiple linear regression analysis method which was processed using Eviews12 software. The results showed that profitability, financial leverage, and age of the company had no significant effect on the first day's profit rate. Meanwhile, underwriter reputation and inflation have a significant effect on the first day's profit rate.